Acetaminophen Protein Adducts in Hospitalized Children Receiving Multiple Doses of Acetaminophen. (17th May 2019) - Jiang, Sibo; Vozmediano, Valvanera; Abdel‐Rahman, Susan M.; Schmidt, Stephan; James, Laura P.
Abstract: Previous reports have questioned the safety of multiple doses of acetaminophen administered to ill children. Acetaminophen protein adducts (adducts) are a biomarker of acetaminophen‐induced liver injury and reflect the oxidative metabolism of acetaminophen, a known mechanism in acetaminophen toxicity. In this prospective observational study, we analyzed adduct concentrations in 1034 blood samples obtained from 181 hospitalized children (1 to 18 years inclusive) who received 2 or more doses of acetaminophen. Linear regression analysis showed that serum adduct concentrations increased as a function of the cumulative acetaminophen dose, which could be attributed, in part, to a long half‐life of adducts (2.17 ± 1.04 days [mean ± standard deviation]) in children. However, few patients (2%) were found to have adduct concentrations higher than 1.0 nmol/mL, a previously identified toxicity cut point for the diagnosis of acetaminophen‐induced liver injury in patients with alanine aminotransferase values exceeding 1000 IU/L. A small cohort of patients with suspected infection was noted to show higher adduct concentrations. In addition, adduct concentrations showed a stronger correlation with cumulative acetaminophen doses in adolescents compared with children ( R 2 = 0.41 vs 0.26). No other covariates (body weight, body mass index z score, sex, race, or surgery) remarkably correlated with adduct elevation. In summary, low levels of adducts can be detected in hospitalized children receiving multiple doses of acetaminophen, and adduct levels correlate with cumulative acetaminophen dose.